A Study on the Difficulties and Factors Affecting the Third Year Students in Enlarging Vocabulary at Senior High School - shabrina, Shabrina; Dahnilsyah, Dahnilsyah; Syarfi, Muhammad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Vocabulary is a key when people learning English. The abilities of reading, writing, listening, and speaking in the target language may be impacted by a lack of vocabulary knowledge. This study aims to discover the difficulties and factors faced in enlarging vocabulary by the third grade students of SMAS IT Mutiara, Duri. The research design was descriptive, and selected using cluster sampling. The samples of this research were 34 students of 185 students at the third grade students of SMAS IT Mutiara. The research instrument of this study were vocabulary difficulty test and questionnaire. The research findings revealed that the percentage of the students’ difficulties in enlarging vocabulary of meaning was (67,56%), antonym was (74,70%), synonym (72,64%), prefixes was (68,52%), and suffixes was (66,46). So, the dominant difficulty in enlarging vocabulary at the third grade of SMAS IT Mutiara, Duri was suffixes.